African Pentecostalism in Britain: migration, inclusion, and the prosperity gospel - Stockland, Katharine (Routledge, 2022)
Based on ethnographic research among African Pentecostal Christians living in the UK, this book addresses themes of migration and community formation, religious identity and practice, and social and political exclusion. With attention to strained kinship relationships, precarious labour conditions, and struggles for legal and social legitimacy, it explores the ways in which intimacy with a Pentecostal God – and with fellow Christians – has been shaped by the challenges of everyday life for Africans in the UK. A study of religious subjectivity and the success of the so-called ‘prosperity’ gospel, African Pentecostalism in Britain examines the manner in which the presence of God is realised for believers through their complex and often-fraught relationships of trust and intimacy with others. As such, it will appeal to sociologists and anthropologists with interests in migration and religion.
paid